A Practical Algorithm for the Management of Superficial Folliculitis of the Scalp: 10 Years of Clinical and Dermoscopy Experience - Michela Starace; João Paulo Yamagata; Rita Fernanda Cortez de Almeida; Simone Frattini; Francesca Bruni; Aurora Alessandrini; Matilde Iorizzo; Daniel Fernandes Melo; Iria Neri; Bianca Maria Piraccini (Dermatology Practical & Conceptual, 2023)
Introduction: Superficial folliculitis of the scalp (SFS) is a common complaint in clinical practice, and initial presentation may be difficult to differentiate as they may appear very similar to each other.